Pengaruh Model Pembelajaran Prediction Guide Terhadap Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran IPA di SMK Negeri 1 Alo’oa Tahun Pelajaran 2023/2024 - Juli Kristiani Telaumbanua (Program Studi Pendidikan Biologi - Universitas Nias, 2024)
Low student motivation and learning outcomes in science subjects remain significant challenges in schools, particularly when learning processes are still dominated by conventional teacher-centered approaches that do not actively engage students. This study aimed to analyze the effect of the Prediction Guide Learning Model on students’ motivation and learning outcomes in science subjects at SMK Negeri 1 Alo’oa during the 2023/2024 academic year. The research was conducted using a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The research subjects consisted of two classes: an experimental class taught using the Prediction Guide model and a control class taught using conventional learning methods. Data were collected through validated learning outcome tests and learning motivation questionnaires, then analyzed using normality tests, homogeneity tests, t-tests, and z-tests. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class, accompanied by a significant increase in learning motivation. Statistical testing confirmed that the Prediction Guide Learning Model had a significant effect on both student motivation and learning outcomes. These findings affirm that prediction-based active learning can serve as an effective strategy for improving the quality of science education.